2011
DOI: 10.1093/jscr/2011.9.10
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of the Inferior Vena Cava

Abstract: We highlight the case of a double Inferior Vena Cava (IVC) encountered in a multi-visceral recovery operation on a deceased donor. In such cases pre-operative abdominal cross sectional imaging is usually not available hence the procurement surgeon needs to rely on vigilance and awareness of other potential anatomical variations that are associated with the condition. We outline our operative approach, summarize the embryological development of IVC and present the case as a reminder of this rare anatomical vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…The double IVC results from persistence of both the left and right supracardinal vein. The literature revealed that usually, the left-sided IVC ends at the level of the left renal vein, crosses over the abdominal aorta to join the rightsided IVC [24]. However, there might be variations in this arrangement [3].…”
Section: Discussionmentioning
confidence: 99%
“…The double IVC results from persistence of both the left and right supracardinal vein. The literature revealed that usually, the left-sided IVC ends at the level of the left renal vein, crosses over the abdominal aorta to join the rightsided IVC [24]. However, there might be variations in this arrangement [3].…”
Section: Discussionmentioning
confidence: 99%
“…The literature also contains many cases in which duplication of the IVC was diagnosed in other situations, such as during autopsy and retroperitoneal surgery (particularly for abdominal aortic aneurysm repair and live donor nephrectomy). 9 , 10 This suggests that not all duplicated IVCs lead to venous thrombosis or PE. Therefore, which type of duplicated IVC is likely to cause venous thrombosis requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Xue et al [24] found a Japanese male cadaver, having a DIVC, in that the left IVC coalesced with the left renal vein and finally ran across in front of the abdominal aorta and drained into the right IVC. Two cases of DIVC were found during renal transplantation: Kennealey et al [9] found a DIVC in a female living renal transplant donor and Raza et al [17] found a DIVC in a male deceased organ donor. Discovery of the anomalous vessels during transplantation caused prolongation of the operative time to re-design the procedure for safety outcomes.…”
Section: Discussionmentioning
confidence: 99%